Changes of Lithuanian Foreign Trade in the Integrated European Union Market - Jatuliavičienė, Gražina; Kučinskienė, Marija; Garuckas, Rimantas (Ekonomika, 2007)
The rapid economic growth of the world countries is associated with the expedited development of foreign trade. Lithuania’s political and economic situation urges to conceive that the country requires active improvement and development of its foreign relations. It is important for Lithuania to occupy its place in the European Union (EU) integrated market. Therefore the aim of this article is to highlight changes in the Lithuanian foreign trade and to foresee the possibilities of improving competitiveness in the integrated market. To present objectively the results of the analysis. data of the Department of Statistics of the Republic of Lithuania, the latest research in the field were taken as a reference. Comparative analysis and summary methods of academic literature, publications and statistical data were applied. In current conditions, a country is able to achieve economic growth only by participating in foreign trade. International economic relations have established most recently in Lithuania and now become extremely important. The key changes of Lithuanian foreign trade policy are concerned with the integration in the EU market and common foreign trade policy. The application of new internal and external market conditions have influenced the country’s foreign trade developments. The EU membership expanded Lithuania’s markets of disposal, formed the background for an increase of foreign trade and the development of economy. After becoming the EU member, Lithuania effects its foreign trade in accordance with the common EU foreign trade policy requirements and measures by modelling the common trade policy together with other Member States. Lithuania’s accession to the EU had a positive impact on the expansion of its foreign trade. Export increased by 18.43% in 2006, and import increased by 22.98% within one year. Regionally, EU Member States are the key Lithuania’s export and import partners. In 2006, the further increase of internal demand encouraged import, therefore, export lagged behind import in terms of the rate of development (4.55 percentage points), and Lithuanian foreign trade deficit amounted to 14262.3 million LtL in 2006 and was further increasing rapidly. In 2006, the key Lithuania’s export partners were Russia (12.8%), Latvia (11.1%), Germany (8.7%), Estonia (6.5%) and the key import partners were Russia (24.4%), Germany (14.8%), Poland (9.6%), Latvia (4.8%). Export growth has been achieved in almost every section of the Combined Nomenclature in 2006. Mineral products (24% and 23.6% respectively) formed the largest part of Lithuania’s import and export, and Lithuania’s production and processing industry ensured the major part of the country’s export (about 60%). In developing its foreign trade, Lithuania still needs to overcome the problems inherent in new participants of the global economy. One of the key problems is the insufficient competitiveness of Lithuania’s industry.